Pemberdayaan Siswa PKBM Permata Paket B melalui Strategi Menerapkan Matematika untuk Pemecahan Masalah Sehari-hari - Yuli Supriani; M. Agus Kurniawan; Endar Evta Yuda Prayogi; Mustoto Mustoto; Mesta Wahyu Nita; Siska Ayu Anggraini; Dedi Lazwardi; Ika Ratna Rosanti; Andri Setiadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The problem addressed in this community service project is the low understanding of PKBM Permata Paket B students in applying mathematics to everyday life. The objective of this study is to improve students' understanding of mathematics through context-based learning, as well as to stimulate their interest and independence in solving problems involving numbers. The method used is a contextual teaching approach involving group discussions, problem-solving exercises, and real-life problem applications. The results show that context-based mathematics learning significantly improved students' understanding of budgeting, expenses, and personal finance management. Students also showed increased active participation in learning activities and a better ability to connect mathematical theory with practical problems in their daily lives. This program also had a positive impact on social empowerment, increasing students' independence in managing their daily lives. However, challenges related to understanding more complex concepts remain, and it is recommended to use more varied methods and extend the learning time in the future.